ESTERASE ACTIVITY AMONG PATIENTS WITH GASTROINTESTINAL DISEASES WORKING AT THE PLANTS PROVIDING STORAGE AND DISPOSAL OF ORGANOPHOSPHORUS COMPOUNDS - A. V. Fomichev; V. V. Miroshnikova; U. S. Chalimov; V. U. Golofeevskiy; A. V. Yazenok; V. G. Kuzmich; K. V. Muzurov; E. V. Malysheva; S. N. Pchelina (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Studies have shown that exposure to organophosphates (OPs) is associated with increased frequency of gastrointestinal diseases. In order to evaluate the effect of dysfunction of detoxification system on the development of gastrointestinal pathology, we studied «esterase status» (activity of acetylcholinesterase, butyrylcholinesterase and paraoxonase 1 (PON1)) among workers at the plants providing storage and disposal of OPs. The enzymatic activity of PON1 was significantly increased in individuals who had prolonged direct contact with the OPs. It was shown that among all gastrointestinal diseases included in this study PON1 activity was increased in patients with chronic esophagitis and chronic gastritis as compared to workers without gastrointestinal diseases (p<0.05), so and with diseased workers who had no direct contact with OPs (p<0.05). Thus, changes in PON1 activity may contribute to development of the gastrointestinal pathology among persons having direct contact with OPs.